Cutting through the hype: evaluating the innovative potential of new educational technologies through business model analysis. (2nd January 2016) - Kalman, Yoram M.
Abstract: In an era when novel educational technologies are constantly introduced to the marketplace, often accompanied by hyperbolic claims that these ground-breaking innovations will transform the educational landscape, decision makers in educational institutions need a methodological approach for examining the innovative potential of new educational technologies. This paper employs a framework based on business model analysis to evaluate the innovative potential of new educational technologies. A short discussion of organisational innovation is followed by a presentation of the business model concept and a framework for analysing the strategic impact of a novel technology on an organisation's business model. The proposed framework is presented in the context of educational organisations in general, and that of higher education and the massive open online course phenomenon in particular. Decision-makers and researchers of innovation in higher education can use this business model analysis framework to systematically evaluate the potential strategic value of an educational technology to a particular higher education institution.